Joint energy consumption optimization method for wing-diesel engine-powered hybrid ships towards a more energy-efficient shipping. (15th April 2022) - Wang, Kai; Xue, Yu; Xu, Hao; Huang, Lianzhong; Ma, Ranqi; Zhang, Peng; Jiang, Xiaoli; Yuan, Yupeng; Negenborn, Rudy R.; Sun, Peiting
Abstract: Wing-diesel engine-powered hybrid ships can effectively reduce fuel consumption and CO2 emissions by using wind energy as the auxiliary driving power. The energy optimization management of the hybrid system can further improve the ship's energy efficiency. To achieve this purpose, it is significant to establish an effective energy consumption model for the energy optimization management of the hybrid system. Therefore, an energy consumption model is established based on the energy conversion analysis of the hybrid power system in this paper. This model can effectively describe the energy consumption of the hybrid ship under different navigational environmental conditions. Then, a joint optimization method of the wing attack angle and of the sailing speed for the hybrid ship is proposed by adopting a swarm intelligence optimization algorithm, in order to reduce energy consumption and CO2 emissions of the hybrid ship under different navigational environmental conditions. Finally, the energy consumption optimization potentials by adopting the hybrid power system and the proposed joint optimization method are analyzed. The results show that the energy consumption and CO2 emissions along a typical route can be reduced by about 4.5%. This study provides an important basis for future practical operations of wing-diesel engine-powered hybrid ships. Highlights: An energy consumption model of wing-diesel engine-powered hybrid ships is established. The wind energy resources analysis and the sailing route division are achieved. A joint optimization method of energy consumption for wing-diesel engine-powered hybrid ships is proposed. The proposed method can reduce ship energy consumption and CO2 emission by about 4.5%.